A reassembled nanoporous gold leaf electrocatalyst for efficient CO2 reduction towards CO. Issue 5 (11th April 2018) - Wen, Xiaosong; Chang, Lin; Gao, Yan; Han, Jianyu; Bai, Zhiming; Huan, Yahuan; Li, Minghua; Tang, Zhiyong; Yan, Xiaoqin
Abstract : The free-standing nanoporous gold leaf has an excellent FE of 90% towards CO and a high mass activity of 20.51 A/g. Abstract : Herein, we prepared a free-standing nanoporous gold leaf (NPGL) catalyst by simple one-step de-alloying of the Au–Ag alloy. It displays a much higher CO Faradaic efficiency (CO FE) of 90% and current density (mass activity) of 20.51 A g −1 as compared to the nonporous gold foil at −1.2 V ( vs. Ag/AgCl).